Trinity Church at Copley Square, ca. 1910 - Unknown (Tufts Archival Research Center, 2005)
Street-level view east of Trinity Church, located at Copley Square between Huntington Avenue to the northwest and St. James Avenue to the southeast. The facade of the church faces southwest towards Copley Square. The Hotel Westminster is located to the southeast of or to the right of the church, at the northeast corner of St. James Avenue and Trinity Place. Several pedestrians are included in the photograph. An automobile is visible near the lower-left corner of the photograph. Electricity lines and poles line Boylston Street. Designed by Henry Hobson Richardson, 1872-77 2 9/16 x 5 1/16, 3 1/8 x 5 1/16 overall Photographs